1972
DOI: 10.1159/000178261
|View full text |Cite
|
Sign up to set email alerts
|

Fractional and Partial Hypopituitarism in Anorexia nervosa

Abstract: Increases in serum growth hormone which characterize acute starvation in non-obese individuals were usually absent in anorexia nervosa. Serum LH was decreased with serum FSH apparently normal in the majority. Increased adrenocortical activity as indicated by high basal 11 (OH)-corticosteroids and their incomplete suppression by dexamethasone and hyperresponsiveness to exogenous ACTH was recorded in about one-half of the patients tested. Urinary steroid responses to intravenous metyrapone were normal in all but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Despite this the plasma concentration of cortisol in patients with AN is actually elevated: In fact, the morning and evening levels of cortisol are usually higher than in healthy subjects, as are the 24-hour mean plasma cortisol concentrations (Alvarez, Dimas, Castro, Rossman, Vanderlaan, & Vanderlaan, 1972;Aro et al, 1977;Bethge et al, 1970;Danowski et al, 1972;Doerr et al, 1980;Frankel &Jenkins, 1975;Garfinkel et al, 1975;Hurd et al, 1977;Landon, Greenwood, Stamp, & Winn, 1966;Marks & Bannister, 1963;Marks, Howorth, & Greenwood, 1965;Swigar, Kolakowska, & Quinlan, 1979;Walsh, Katz, Levin, Kream, Fukushima, Hellman, Weiner, & Zumoff, 1978;Warren & Vande Wiele, 1973). Furthermore, raised levels of "free" cortisol are present in the urine Walsh et al, 1978), suggesting an increase in cortisol production by the adrenal glands but a diminished clearance of its metabolites in AN.…”
Section: Urinary Levels Of 17-hydroxycortico-and 1 7-keto-steroids Anmentioning
confidence: 99%
“…Despite this the plasma concentration of cortisol in patients with AN is actually elevated: In fact, the morning and evening levels of cortisol are usually higher than in healthy subjects, as are the 24-hour mean plasma cortisol concentrations (Alvarez, Dimas, Castro, Rossman, Vanderlaan, & Vanderlaan, 1972;Aro et al, 1977;Bethge et al, 1970;Danowski et al, 1972;Doerr et al, 1980;Frankel &Jenkins, 1975;Garfinkel et al, 1975;Hurd et al, 1977;Landon, Greenwood, Stamp, & Winn, 1966;Marks & Bannister, 1963;Marks, Howorth, & Greenwood, 1965;Swigar, Kolakowska, & Quinlan, 1979;Walsh, Katz, Levin, Kream, Fukushima, Hellman, Weiner, & Zumoff, 1978;Warren & Vande Wiele, 1973). Furthermore, raised levels of "free" cortisol are present in the urine Walsh et al, 1978), suggesting an increase in cortisol production by the adrenal glands but a diminished clearance of its metabolites in AN.…”
Section: Urinary Levels Of 17-hydroxycortico-and 1 7-keto-steroids Anmentioning
confidence: 99%
“…Russell et al (1965) measured decreased levels of urinary estrogens in females with anorexia nervosa. Danowski et al (1972) found low 17-ketosteroids and Porter-Silber chromogens in the urine. Urinary gonadotrophin activity is also consistently subnormal.…”
mentioning
confidence: 91%
“…Increased motor activity, even in the face of severe cachexia, is characteristic of these individuals. Females with anorexia nervosa demonstrate an absence of normal menstrual functioning, often preceding or concurrent with the onset of anorexia, and usually preceding cachexia (Theander, 1970;Frazier, 1965; Beumont, !970; Hart et at., t970;Danowski et al, 1972;Lakoff, Feldman, 1972). Although the disease is more common in females, males may develop anorexia nervosa, and in such males, development of secondary sexual characteristics is delayed and sexual interest declines (Bruch, 1971;Crisp, Toms, 1972).…”
mentioning
confidence: 99%
“…Although more common in the opposite order, anorexia nervosa can predate the onset of diabetes. In fact, diabetic glucose tolerance curves have been shown in anorexia nervosa (Danowski, Livstone, & Gonzales, 1972;Ross, 1938;Sheldon & Young, 1938;Warren & Vande Wiele, 1973) and in starvation (Baig & Edozien, 1965;Bowie, 1964). Furthermore, low plasma insulin levels were observed in women with anorexia, resulting from high insulin clearance rather than from depressed insulin secretion (Letiexhe, Scheen, & Lefebvre, 1997).…”
Section: Discussionmentioning
confidence: 99%